Development of a Sustainable Walkway System and Its Performances Analysis of Voltage, Current, and Power Output - Abu Bakar, Ahmad Adnan; Salimin, Suriana (Evolution in Electrical and Electronic Engineering, 2025)
This project designs a sustainable walkway using piezoelectric materials to capture energy from pedestrian movements. It converts human mechanical energy into electricity with piezoelectric tiles. The study involved developing these tiles, choosing materials, and measuring power output. Results indicated that an array of twelve piezo discs generated up to 128.74 mW, highlighting their significant potential for renewable energy applications in urban areas. This system supports sustainable urban development and highlights the feasibility of using piezoelectric technology in urban infrastructure. Future work could expand applications and integrate with other renewable energy systems.